C-1 Substituted isoquinolines potentiate the antimycobacterial activity of rifampicin and ethambutol - Liam T. Martin; Liam T. Martin; Eleanor D. Lamming; Arundhati Maitra; Parisa N. Mortazavi; Rebecca Roddan; Rebecca Roddan; John M. Ward; Sanjib Bhakta; Helen C. Hailes (Frontiers Media S.A., 2023)
IntroductionThe emergence of extensively drug-resistant strains of Mycobacterium tuberculosis threatens decades of progress in the treatment of a disease which remains one of the leading infectious causes of death worldwide. The development of novel antimycobacterial compounds is therefore essential to reinforce the existing antitubercular drug discovery pipeline. There is also interest in new compounds which can synergize with existing antitubercular drugs and can be deployed as part of a combination therapy. This strategy could serve to delay the emergence of resistance to first-line anti-tuberculosis drugs and increase their efficacy against resistant strains of tuberculosis. Previous research has established that several C-1 substituted tetrahydroisoquinolines have antimycobacterial activity. Here we sought to expand our understanding of their antimycobacterial structure activity relationships and their potential to act as adjunct therapies alongside existing antitubercular drugs.MethodsThree chemical series were synthesised and assayed for their antimycobacterial potency, mammalian cell toxicity, inhibition of whole-cell efflux and synergism with isoniazid, rifampicin, and ethambutol.ResultsSeveral compounds were found to inhibit the growth of mycobacteria. Potent inhibitors of whole-cell efflux were also identified, as well as compounds which exhibited synergism with rifampicin and ethambutol.ConclusionsStructure-activity relationships were identified for antimycobacterial potency, improved selectivity, whole cell efflux inhibition and synergism. Potent whole-cell efflux inhibitors and synergistic compounds were identified, suggesting potential development as adjuncts to existing anti-tuberculosis chemotherapy.